Role of Religion in Socio-cultural transformation in 19th century Jaffna – A Socio-anthropological Analysis - Rajeskannan, R (M.Phil. in Sociology, 2012)
In social transformation and social mobility, religion plays a significant role; as a consequence it has become an important area of research interest in Sociology. Sociology of religion considers the internal changes of religion at micro level and the impact of religion on the society at micro level. Anthropological perspective gives an in-depth insight of comparative cultural understanding. Classical studies of Max Weber, Malinowski, Durkheim and the ethno methodological studies of Mc Kim Marriot and M.N.Srinivas in social anthropology are significance in this regard. As far as Sri Lanka is concerned, 19th century is a period when important changes took place in its social history. The colonial rule of this period gave rise to major socio cultural transformation in Jaffna, which resulted in changes at all layers of the society. The present study examines the role of religion in the process of transformation. The changes that occurred in the 19th century are continuing even to this day. Understanding these changes is very significant in constructing a knowledge base for social and cultural development planning. This research records the colonial social history of Jaffna, through the perspective of sociology and anthropology on religion with the application of historical sociological approach. As such data is obtained from historical records, travel notes, diaries, memoirs, and books on history, pamphlets, oriental writings and case studies of the key personalities who act as catalysts of transformation. The above data is analyzed through content analysis method in the light of appropriate sociological and anthropological theories. In addition to the grand theories of Max Weber and Talcott Parsons, it pays great attention to oriental theories as well. This study reveals the impact of religion on the large scale changes in the social structure and culture. When the early period under foreign rule is compared with that of the 19th century, the latter though with conflicts, was one of tolerance. The indigenous religions while preserving their traditions absorbed the changes that were taking place. In the mean time oriental Saiva religion has taken a reformist trend to meet the challenges experienced and molded itself as a form of ‘potestant saivism’ similar to the condition referred by Gombrich and Gananath (1990) on Buddhism of that day as protestant Buddhism. The Christian religion paved the path for changes but at the same time was drowned within the indigenous traditions. In spite of the fact modernization and westernization took place, oriental values received priority. Personalities like Navalar and new social institutions emerged. These all occurred on the basis of religion, and they became key forces. The religion through education brought about major changes like, middle class formation, elite formation, occupational mobility and politicization. Religion also had its influence on liberalization, democratization and social equality. At the same time, traditional aspects like social stratification continued to be maintained. The new religions that accompanied modernity came to be under the influence of the indigenous culture. As a consequence these religions could not bring a complete transformation and a dualism is found to exist in the socio cultural transformation of the Jaffna society between the process of indigenization and the process of universalization to this date.